The Role of Cooperatives in Stabilizing Palm Oil FFB Prices and Their Impact on Member Welfare (Case Study in Kud Makmur Jaya, Baringin Jaya Village, District Torgamba, South Labuhanbatu Regency, North Sumatra) - Ningsih, Anggun Widya; Bidarti, Agustina (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2022)
ABSTRACT This study aims to: 1) To identify the causes of instability in palm oil FFB prices in Baringin Jaya Village, Torgamba District, southern Labuhanbatu Regency. 2) To identify the role of cooperatives in stabilizing palm oil FFB prices from their relation to cooking oil prices in KUD Makmur Jaya Beringin Jaya Village, Torgamba District, southern Labuhanbatu Regency. 3) To analyze the effect of unstable palm oil FFB prices on the welfare of KUD Makmur Jaya members. This research was conducted at KUD Makmur Jaya, Beringin Jaya Village, Torgamba District, South Labuhanbatu Regency. This location determination is carried out intentionally (Purposive) based on information and considerations related to existing problems. The study was conducted in August 2022 using simple random sampling and snowball sampling methods. Based on the results of the study, the instability of palm oil FFB prices in Baringin Jaya Village occurs due to world market factors and also the government's duberi pricing system, cooperatives play a role in formulating prices together with administrators and supervisors to stabilize FFB prices where prices are determined based on market prices, FFB quality, consumer satisfaction and can compete with other business units. KUD Makmur Jaya also does good marketing and good management of oil palm plantations as well. The unstable price of FFB has a significant effect on the welfare of KUD Makmur Jaya members. (both farm income, access to health facilities and access to education) Keyword: KUD Makmur Jaya, Palm Oil FFB Price, Member Welfare